PENGARUH KEPRIBADIAN, LINGKUNGAN DAN KETERSEDIAAN INFORMASI KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA ANAK MUDA DI KOTA JAYAPURA - Rut Penina Somisu (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
An individual is motivated to engage in activities when they are enthusiastic. The purpose of this study was to determine the influence of personality, social environment, and access to entrepreneurial information on entrepreneurship intentions among youth in the city of Jayapura, Indonesia. 397 respondents between the ages of 15 and 34 were analysed using a variety of linear regression analysis techniques. It was concluded that personality, social environment, and access to entrepreneurial information partially and simultaneously had a positive effect on the interest in entrepreneurship of young people in the city of Jayapura.